Lymph node pooling: a feasible and efficient method of lymph node molecular staging in colorectal carcinoma. Issue 1 (December 2017) - Rakislova, Natalia; Montironi, Carla; Aldecoa, Iban; Fernandez, Eva; Bombi, Josep; Jimeno, Mireya; Balaguer, Francesc; Pellise, Maria; Castells, Antoni; Cuatrecasas, Miriam
Abstract Background Pathologic lymph node staging is becoming a deficient method in the demanding molecular era. Nevertheless, the use of more sensitive molecular analysis for nodal staging is hampered by its high costs and extensive time requirements. Our aim is to take a step forward in colon cancer (CC) lymph node (LN) pathology diagnosis by proposing a feasible and efficient molecular method in routine practice using reverse transcription loop-mediated isothermal amplification (RT-LAMP). Results Molecular detection of tumor cytokeratin 19 (CK19) mRNA with RT-LAMP was performed in 3206 LNs from 188 CC patients using two methods: individual analysis of 1449 LNs from 102 patients (individual cohort), and pooled LN analysis of 1757 LNs from 86 patients (pooling cohort). A median of 13 LNs (IQR 10–18) per patient were harvested in the individual cohort, and 18 LNs (IQR 13–25) per patient in the pooling cohort (p ≤ 0.001). The median of molecular assays performed in the pooling cohort was 2 per patient (IQR 1–3), saving a median of 16 assays/patient. The number of molecular assays performed in the individual cohort was 13 (IQR 10–18), corresponding to the number of LNs to be analyzed. The sensitivity and specificity of the pooling method for LN involvement (assessed by hematoxylin and eosin) were 88.9% (95% CI 56.5–98.0) and 79.2% (95% CI 68.9–86.8), respectively; concordance, 80.2%; PPV, 33.3%; NPV, 98.4%. The individual method had 100% sensitivity (95% CI 72.2–100), 44.6% specificity (95% CI 34.8–54.7), 50% concordance, 16.4% PPV, and 100% NPV. The amount of tumor burden detected in all LNs of a case, or total tumor load (TTL) was similar in both cohorts (p = 0.228). Conclusions LN pooling makes it possible to analyze a high number of LNs from surgical colectomies with few molecular tests per patient. This approach enables a feasible means to integrate LN molecular analysis from CC specimens into pathology diagnosis and provides a more accurate LN pathological staging with potential prognostic implications.